Emerging Tools for Stroke Prevention in Atrial Fibrillation - Christos Voukalis; Gregory Y.H. Lip; Eduard Shantsila (EBioMedicine, 2016)
Ischaemic strokes resulting from atrial fibrillation (AF) constitute a devastating condition for patients and their carers with huge burden on health care systems. Prophylactic treatment against systemic embolization and ischaemic strokes is the cornerstone for the management of AF. Effective stroke prevention requires the use of the vitamin K antagonists or non-vitamin K oral anticoagulants (NOACs). This article summarises the latest developments in the field of stroke prevention in AF and aims to assist physicians with the choice of oral anticoagulant for patients with non-valvular AF with different risk factor profile.